Katniss’ Savior: Wilderness in Suzanne Collins’s 'The Hunger Games' - Sa'adah, Sufi Ikrima; Febrianti, Cyintia; Ariyanti, Della; Akbar, Dewa Maulana (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
From many discussions on wilderness in literary works, only a few focus on the young adult dystopian, even more on Suzanne Collins’s The Hunger Games. For this reason, this article aims to portray the wilderness in the book as the survival resource since the previous studies fail to point out such an issue. This recent study is conducted by descriptive qualitative methods. As the theoretical basis, the discussion employs Garrard’s account of wilderness and Ross’s myth of wilderness in American literature. As a result, the discussion depicts the wilderness as the natural woodland surrounding District 12 and the artificial battleground of the Games in Panem. The woods in Katniss’s district enable her to provide for her family and develop such literacy in the wilderness. This literacy is advantageous in the Games arena, thus helps Katniss to be one of the winners. The findings might provide such an insight to the reader to live harmoniously with nature, even more with the wilderness.